Financial statement analysis and security valuation - Penman, Stephen H. (New York : McGraw-Hill/Irwin, 2010)
This book presents the principles of financial statement analysis, with a focus on the investor. Many types of investment are entertained. Buying a firm's equity-its common stock- is one, and the book has a particular focus on the shareholder and prospective shareholder. Buying a firm's debt - its bonds - is another. The shareholder is concerned with profitability, the bondholder with default, and financial statement analysis aids in evaluating both. Banks making loans to firms are investors, and they are concerned with default. Firms themselves are also investors when they consider strategies to acquire other firms, go into a new line of business, spin off a division or restructure, or indeed acquire or disinvest in an asset of any form. In all cases financial statement must be analyzed to make a sound decision.
Includes bibliographical references and index.
rpm 09/07/13
Loans
Keywords: Financial statements; Security valuation; Financial analysis